2016
DOI: 10.1186/s12906-016-1279-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro antibacterial activity of the solvent fractions of the leaves of Rhamnus prinoides L’Herit (Rhamnaceae) against pathogenic bacteria

Abstract: BackgroundMedicinal plants play great roles in the treatment of various infectious diseases. Rhamnus prinoides is one of the medicinal plants used traditionally for treatment of bacterial diseases. The antibacterial activity of the crude extract of the plant had been shown by a previous study, but this study was undertaken to further the claimed medicinal use of the plant by screening its solvent fractions for the said activity so that it could serve as a basis for subsequent studies.MethodsThe solvent fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
52
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 27 publications
8
52
7
Order By: Relevance
“…On the other hand, results of the current study were contrasted with that of [6] and [26] who reported aqueous extract of Rhamnus prinoides leaves was found to be devoid of antibacterial activities against all the test bacterial strains regardless of the concentrations. Another study conducted by [3] reported that, water extracts of Avicennia marina did not give any inhibition against Staphylococcus sp.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…On the other hand, results of the current study were contrasted with that of [6] and [26] who reported aqueous extract of Rhamnus prinoides leaves was found to be devoid of antibacterial activities against all the test bacterial strains regardless of the concentrations. Another study conducted by [3] reported that, water extracts of Avicennia marina did not give any inhibition against Staphylococcus sp.…”
Section: Discussioncontrasting
confidence: 99%
“…Among extracts of the plant used in the study, the ethanol extract of Rhamnus prinoides fruits showed the maximum zone of inhibition which was in line with the study of [33] The current results were disagreed with that of [26] aureus were 400 mg/ml and 200 mg/ml respectively [6].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations